Comparative Evaluation of Chiller System Performance with and Without Smart Chiller Control Implementation - Muhammad Dzian Akbar Firdaus; Muhammad Akmal; Luga Martin Simbolon (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
Chiller systems are a major component of HVAC systems and account for a significant portion of building energy consumption; therefore, efforts to improve efficiency are required through the implementation of Smart Chiller Control. This study aims to evaluate the performance of chiller systems before and after the implementation of Smart Chiller Control based on cooling capacity, power consumption, Energy Efficiency Ratio (EER), efficiency ratio (kW/TR), and power savings. The study utilized actual operational data from three chiller groups, namely CG03, CG09, and CG15. The results showed that cooling capacity increased from 6,664.17 kW to 8,167.02 kW for CG03, from 8,035.03 kW to 10,894.99 kW for CG09, and from 7,296.20 kW to 8,109.69 kW for CG15. The EER values increased from 14.74 to 15.76 for CG03, from 16.47 to 19.55 for CG09, and from 15.49 to 17.60 for CG15, while the kW/TR values decreased from 0.81 to 0.76 for CG03, from 0.72 to 0.61 for CG09, and from 0.77 to 0.68 for CG15. Baseline predictions using linear regression indicated power savings of 106.73 kW (6.92%) for CG03, 218.57 kW (13.09%) for CG09, and 171.51 kW (11.30%) for CG15. The findings demonstrate that Smart Chiller Control can improve both the performance and energy efficiency of chiller systems.